MATERNAL AND CHILD CARE IN THE DIAGNOSIS AND TREATMENT OF CONGENITAL SYPHILIS IN BRAZIL: AN INTEGRATIVE LITERATURE REVIEW (CIPEEX, 2022)
SYPHILIS IS A DISEASE CAUSED BY TREPONEMA PALLIDUM, WHICH IS MAINLY SEXUALLY TRANSMITTED. HOWEVER, IN UNTREATED PREGNANT WOMEN, IT CAN OCCUR TRANSPLACENTALLY. IN THIS CONTEXT, ALTHOUGH THERE IS FREE TREATMENT PROVIDED BY THE UNIFIED HEALTH SYSTEM, THERE ARE FACTORS THAT PREVENT THE ERADICATION OF CONGENITAL SYPHILIS TROUGHOUT THE BRAZILIAN TERRITORY. THUS, THIS REVIEW AIMS TO ANALYZE THE FACTORS THAT PREVENT THE ERADICATION OF THE CONSEQUENCES CAUSED BY TREPONEMA PALLIDUM ON THE WELL-BEING OF THE NEWBORN THROUGHOUT THE BRAZILIAN MACRO-REGIONS. AS FOR THE METHODOLOGY, AN INTEGRATIVE LITERATURE REVIEW WAS CARRIED OUT, COVERING 19 ARTICLES, HAVING AS INCLUSION CRITERIA ORIGINAL ARTICLES, WITH ETHICAL PRECEPTS, WHICH COMPRISE THE BRAZILIAN MACRO-REGIONS, PUBLISHED BETWEEN 2012 AND 2022, IN PORTUGUESE AND FREE OF CHARGE. AS EXCLUSION CRITERIA, THERE WERE CASE REPORTS, LETTERS TO THE READER, LETTERS TO THE EDITOR AND MONOGRAPH. TO ELABORATE THE GUIDING QUESTION, THE PEAK STRATEGY WAS USED. AS A RESULT, IT WAS ANALYZED THAT ISSUES RELATED TO ADHERENCE TO PRENATAL CARE, INADEQUATE TREATMENT, AND SOCIOECONOMIC FACTORS WERE THE ONES THAT MOST INTERFERED IN THE PERPETUATION OF CONGENITAL SYPHILIS. THEREFORE, WHEN ANALYZING THE ARTICLES, IT WAS OBSERVED THAT IT IS NECESSARY TO ADOPT SOME MEASURES TO REDUCE SYPHILIS RATES, SUCH AS EXPANDING ACCESS AND QUALITY ASSISTANCE TO INDIVIDUALS.
Keywords: sífilis congênita; treponema pallidum; cuidados pré-natal